Effects of sprint versus strength training on risk factors for hamstring injury in football players - Sancese, A.; Taylor, L.; Walsh, G.; Byrd, E.; Delextrat, A. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: This study aimed to compare the effects of in-season sprint training vs. Nordic hamstring exercise (NHE) training on risk factors for hamstring strain injuries (HSI). METHODS: Eighteen male university football players (20.9±2.5 years; 181±7 cm; 75.8±9.1 kg; 15.2±3.5% of body fat) were randomly allocated to a sprint group or NHE group. They completed baseline isokinetic strength and sprint mechanics assessments prior to their assigned intervention performed twice weekly for 4-weeks, before post-testing. A mixed design ANOVA with repeated measures assessed time, group and interaction effects for all risk factors. RESULTS: There were significant increases in hamstring eccentric peak torque at 60°·s-1 (+8% - 9.9%), the torque produced at 20° (+15%) and 10° (+21% - 31%), as well as a rightward shift in angle of peak torque towards knee extension (-27% - -36%) in both groups (P<0.05). We also observed a significant increase (+24.5%) in hamstring eccentric peak torque at 180°·s-1 in the strength group only and significant improvements (+29.4%) in the rate of torque development of the dominant leg at 60°·s-1 in the sprint group only (P<0.05). No significant effect was noted on sprint performance or sprint mechanics (P>0.05). CONCLUSIONS: These findings suggest that both training programs can be effective to mitigate the risk of HSI, but through different mechanisms.